1994
DOI: 10.3109/10826089409047912
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Administration of Naloxone Is as Effective as the Intravenous Route in Opiate Addicts

Abstract: Naloxone is used intravenously in opiate addiction in emergency cases, in rapid opiate detoxification, and as a diagnostic tool. This is a study comparing the efficacy of intranasal naloxone to other routes (intravenous/intramuscular) in 17 opiate-dependent patients. The nasal drug administration of naloxone was found to be as effective as the intravenous route. The nasal drug application offers a wide margin of safety for patients and medical staff, especially in emergency situations in regard to infection ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 10 publications
1
44
0
3
Order By: Relevance
“…Preclinical data from rodent studies showed complete absorption of nasal naloxone (bioavailability relative to IV: F% = 101%; Hussain et al, 1984). In first in-human trials, nasal naloxone was found to elicit withdrawal symptoms in opioid-dependent volunteers (Loimer et al, 1992(Loimer et al, , 1994. Since the early 2000s, nasal naloxone has been used off-label by ambulance personnel (Barton et al, 2005(Barton et al, , 2002Belz et al, 2006;Kelly et al, 2005;Kerr et al, 2009;Merlin et al, 2010;Robertson et al, 2009;Weber et al, 2012) and in the emergency department (Sabzghabaee et al, 2014).…”
Section: Sublingualmentioning
confidence: 99%
“…Preclinical data from rodent studies showed complete absorption of nasal naloxone (bioavailability relative to IV: F% = 101%; Hussain et al, 1984). In first in-human trials, nasal naloxone was found to elicit withdrawal symptoms in opioid-dependent volunteers (Loimer et al, 1992(Loimer et al, , 1994. Since the early 2000s, nasal naloxone has been used off-label by ambulance personnel (Barton et al, 2005(Barton et al, , 2002Belz et al, 2006;Kelly et al, 2005;Kerr et al, 2009;Merlin et al, 2010;Robertson et al, 2009;Weber et al, 2012) and in the emergency department (Sabzghabaee et al, 2014).…”
Section: Sublingualmentioning
confidence: 99%
“…After dual review of abstracts and titles, 202 articles were selected for full-text dual review, and 13 studies were determined to meet inclusion criteria and were included in this review. We identified three RCTs (n=100 to 182) [37][38][39] and four cohort studies (n=93 to 609) [40][41][42][43] that compared different routes of naloxone administration.…”
Section: Results Of Literature Searchesmentioning
confidence: 99%
“…Observational studies were of very limited usefulness for informing route of administration comparisons, due to serious methodological shortcomings, including failure to adjust for potential confounders. [40][41][42][43] In addition, the route of administration comparisons varied across the studies.Evidence was insufficient to determine how comparative benefits and harms of different routes of naloxone administration differed according to demographics or clinical factors, such as the type and dose of opioid involved in overdose (including whether fentanyl or a fentanyl analogue was involved), presence of other drugs or substances, estimated time since overdose, concomitant psychiatric comorbidities, or prior overdose episodes. There was also insufficient evidence to determine how the type or training of EMS personnel administering naloxone impacted comparisons involving different routes of administration or doses of naloxone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of naloxone by bystanders is reported in over a dozen feasibility studies with reversal rates ranging from 75 to 100 % of cases [15,16,[19][20][21][22][23][24][25][26][27][28][29][30]. Two studies measured the impact of a naloxone program on mortality rates.…”
Section: Introductionmentioning
confidence: 99%